2017
DOI: 10.1002/anie.201611574
|View full text |Cite
|
Sign up to set email alerts
|

Total Synthesis of (−)‐Tetrodotoxin and 11‐norTTX‐6(R)‐ol

Abstract: The enantioselective total synthesis of (-)-tetrodotoxin [(-)-TTX] and 4,9-anhydrotetrodotoxin, which are selective blockers of voltage-gated sodium channels, was accomplished from the commercially available p-benzoquinone. This synthesis was based on efficient stereocontrol of the six contiguous stereogenic centers on the core cyclohexane ring through Ogasawara's method, [3,3]-sigmatropic rearrangement of an allylic cyanate, and intramolecular 1,3-dipolar cycloaddition of a nitrile oxide. Our synthetic route … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0
2

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(19 citation statements)
references
References 43 publications
0
17
0
2
Order By: Relevance
“…1119 “Tetrodamine” ( 2 , Scheme 1a) is a common conceptual target in tetrodotoxin syntheses. 1118 The C6–C7–C8–C8a stereotetrad comprises a challenging functional group constellation. The C7/C8 syn diol is suggestive of a cis alkene difunctionalization; direct dihydroxylation of a suitably substituted benzene has been suggested as a potential entry point for tetrodotoxin 20 and OsO 4 -catalyzed alkene functionalization was realized en route to 1 .…”
mentioning
confidence: 99%
“…1119 “Tetrodamine” ( 2 , Scheme 1a) is a common conceptual target in tetrodotoxin syntheses. 1118 The C6–C7–C8–C8a stereotetrad comprises a challenging functional group constellation. The C7/C8 syn diol is suggestive of a cis alkene difunctionalization; direct dihydroxylation of a suitably substituted benzene has been suggested as a potential entry point for tetrodotoxin 20 and OsO 4 -catalyzed alkene functionalization was realized en route to 1 .…”
mentioning
confidence: 99%
“…Alkaloid 19 was also a major product in another synthesis of TTX by Isobe group in 2004–2006, as well as a minor product in the TTX synthesis by the Fukuyama group in 2017, see Sections 5.3.1 and 5.4.4, respectively. Both racemic and optically active alkaloid 19 was also obtainedas an advanced intermediate during yet another total synthesis of TTX by Sato in 2005 and 2008, cf.…”
Section: Synthesis Of Ttx Analoguesmentioning
confidence: 99%
“…A recent total synthesis of (−)‐TTX was completed by Fukuyama in 2017 and represented, at that time, the shortest total synthesis of the natural product …”
Section: Synthesis Of Ttxmentioning
confidence: 99%
“…Although several total syntheses and many synthetic studies of tetrodotoxin have been reported to date, it deserves further synthetic efforts even today since biological and chemical behaviors of the densely functionalized molecules have not been fully controlled. Since our total synthesis of tetrodotoxin was reported in 2017, we have been pursuing investigations toward this attractive molecule with quite different synthetic strategies. Herein we disclose our novel total synthesis of tetrodotoxin.…”
Section: Figurementioning
confidence: 99%